Visual mapping of team dynamics and communication patterns on surgical ward rounds: an ethnographic study. Issue 10 (9th February 2021) - Bonaconsa, Candice; Mbamalu, Oluchi; Mendelson, Marc; Boutall, Adam; Warden, Claire; Rayamajhi, Shreya; Pennel, Tim; Hampton, Mark; Joubert, Ivan; Tarrant, Carolyn; Holmes, Alison; Charani, Esmita
Abstract : Background: The effect of team dynamics on infection management and antimicrobial stewardship (AMS) behaviours is not well understood. Using innovative visual mapping, alongside traditional qualitative methods, we studied how surgical team dynamics and communication patterns influence infection-related decision making. Materials/methods: Between May and November 2019, data were gathered through direct observations of ward rounds and face-to-face interviews with ward round participants in three high infection risk surgical specialties at a tertiary hospital in South Africa. Sociograms, a visual mapping method, mapped content and flow of communication and the social links between participants. Data were analysed using a grounded theory approach. Results: Data were gathered from 70 hours of ward round observations, including 1024 individual patient discussions, 60 sociograms and face-to-face interviews with 61 healthcare professionals. AMS and infection-related discussions on ward rounds vary across specialties and are affected by the content and structure of the clinical update provided, consultant leadership styles and competing priorities at the bedside. Registrars and consultants dominate the discussions, limiting the input of other team members with recognised roles in AMS and infection management. Team hierarchies also manifest where staff position themselves, and this influences their contribution to active participation in patient care. Leadership styles affect ward-round dynamics, determining whether nurses and patients are actively engaged in discussions on infection management and antibiotic therapy and whether actions are assigned to identified persons. Conclusions: The surgical bedside ward round remains a medium of communication between registrars and consultants, with little interaction with the patient or other healthcare professionals. A team-focused and inclusive approach could result in more effective decision making about infection management and AMS.